Giving Classical Music Therapy to Reduce Pain Intensity in Post Sectio Caesarea Patients - Iif Taufiq El Haque; Elis Roslianti; Heni Heryani; Desry Desry (LPPM STIKes Muhammadiyah Ciamis, 2022)
Objective: This case study aims to examine the effect of classical music therapy interventions on patients undergoing caesarean sections. Method: The approach chosen for the study is a descriptive method using a case study approach and nursing care approach that involves assessment, formulating nursing diagnoses, implementing interventions, and evaluating carried out for 3 days in the Lotus 2 room BLUD RSU Banjar City and referring to the SDKI, SLKI, and SIKI books. This case study research used one patient to be used as a subject, and the selection of participants used accidental sampling. Data collection techniques used by the author include interviews, observation, physical examination, and documentation studies using the SOAPIER method. Result: Nursing diagnosis Acute pain related to physical injury agents (surgery, birth canal trauma, episiotomy) with the diagnosis number D.0077 The patient experiences pain in the wound area post-sectio caesarea surgery in the abdominal region, which is indicated by the patient's complaint. They mention that pain is felt when engaging in excessive movement, there is a postoperative wound in the abdominal area, and the patient grimaced when moving. The pain scale is 8 (0–10), and with intervention given for 3 days with a duration of 15 minutes a day, acute pain nursing problems, which were originally a scale of 8 (0–10), have decreased to a scale of 4 (0–10). Conclusion: There is evidence to suggest that the use of classical music therapy can help reduce pain in patients who have had a caesarean section. From May 31, 2023, to June 2, 2023, nursing interventions involving classical music therapy were carried out for 15 minutes each day. During this period, the patient's pain decreased from level 8 on a scale of 0 to 10 to level 4 on the same scale. These changes indicate that the acute pain has been partially relieved.